Effects of organic loading and oil-grease for the treatment of edible oil effluent in a pilot-scale upflow anaerobic sludge blanket process - Saatci, Y; Hasar, H; Cici, M (Inderscience Enterprises Ltd, 2002)
In this study, Karadeniz Birlik Dogan Erdil vegetable oil factory, Elazig City, Turkey, was selected as representative of this sector. During the first part of the test programme, the quality of raw effluents was investigated. The removals of COD and oil-grease were above 85% at organic loadings between 1.62 and 7.83 kg COD m(-3) d(-1) at hydraulic retention times of 2.0 and 2.5 days. The conversion rates of the removed COD into methane gas were between 0.24 and 0.361 g CH4 (g COD)(-1).
Keywords: edible oil effluent; methane; oil-grease; organic loading; upflow anaerobic sludge blanket